THE EFFECT OF DIGITAL THINK-PAIR-SHARE STRATEGY VIA PADLET ON EFL STUDENTS' SPEAKING SKILLS AT SMKN 5 ENREKANG - Dian Amanda; Ismail; Sri Rosmiana; Asbar; Umiyati Jabri (STKIP Subang, 2026)
This research investigated the effect of the Digital Think-Pair-Share (TPS) strategy via Padlet on the speaking skills of eleventh-grade EFL students at SMKN 5 Enrekang. Speaking was identified as a persistent challenge for vocational high school students, who frequently demonstrated limited fluency, restricted vocabulary, inaccurate pronunciation, and high speaking anxiety as a result of teacher-centered instruction. A quantitative quasi-experimental design was employed, involving 45 students divided into an experimental group (n = 22), taught using Digital TPS via Padlet, and a control group (n = 23), taught using the Role Play method. Both groups completed a pre-test and a post-test assessed through a speaking rubric covering fluency, pronunciation, vocabulary, and grammatical accuracy. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, Levene's homogeneity test, and paired and independent samples t-tests with SPSS version 25. The results showed that the experimental group's mean score increased from 46.45 to 64.14, a gain of 17.69 points, whereas the control group improved only marginally from 39.78 to 41.61. The independent samples t-test yielded t = 5.040, df = 34.500, p < .001, with a mean difference of 22.53 points favoring the experimental group, while the paired samples t-test confirmed a significant pre-to-post improvement in the experimental group (p < .001) but not in the control group (p = .586). These findings indicate that the Digital Think-Pair-Share strategy via Padlet was significantly more effective than the Role Play method in enhancing EFL students' speaking skills. The study recommends that English teachers adopt Digital TPS via Padlet as a structured, technology-supported, and student-centered approach to speaking instruction in vocational secondary schools.